BASIC MIND MAPPING ON MASTERING LISTENING SKILLS FOR COMMUNICATION ON ASEAN ECONOMIC COMMUNITY (AEC) AND 4.0 ERA (PEMETAAN KONSEP DASAR PENGUASAAN KEAHLIAN MENYIMAK UNTUK KOMUNIKASI PADA MASYARAKAT EKONOMI ASEAN DAN ERA 4.0) - Herfyna Asty; Edwar Kemal; Siska Siska; Wahyudi Rahmat; Song Doo Jin (Universitas PGRI Sumatera Barat, 2021)
Since 2015, Asean Economic Community has +been implemented in Indonesia. One of the great changes is using English for communication. English has still been a foreign language for Indonesian people. Consequently, English is learned and started in kindergarten from university to make Indonesian people familiar with English. Listening becomes a difficult subject for the students because they could not answer the questions and they got bad grades for examination. It was to find out what the need analysis important for the teacher and students to study English. It used a descriptive qualitative method with the instruments such as questionnaires, document checklists, and interviews. The population of the research was 72 students and the sampling was total sampling. After analyzing the data, from the questionnaire filled up by students, it is found that almost all students agree about the items of teaching materials proposed by Hutchinson and Water. The results are 92.75% for 2016 A, 98.87% for 2016 B, and 92.46 % for 2016 C. The total is 94.69% of students agree with the teaching material. From the document, checklist shows that the teaching materials used on the Listening subject have not fulfilled provide a stimulus to learning, help to organize the teaching-learning process, use nature of language and learning, provide nature of learning task, broadening the teacher’s knowledge, and provide correct and appropriate language use. Interview information shows that teaching materials for Listening subjects are a combination of many sources without being analyzed and investigated by lecturers. Finally, the most important aspect is an appropriate teaching material must be made to fulfill the learning outcomes.